Profile of women seeking medical termination of pregnancy in South India. Issue 3 (5th March 2014) - Holla, Ramesh; Kanchan, Tanuj; Unnikrishnan, Bhaskaran; Kotian, Mangalore Shashidhar; Kumar, Nithin; Thapar, Rekha; Mithra, Prasanna; Papanna, Mohan Kumar; Kulkarni, Vaman; Darshan, Bhagawan Bhagyamma
Abstract: Objective: To investigate the demographic and obstetric profile of women seeking medical termination of pregnancy (MTP) in South India in accordance with the MTP Act of India. Methods: A registry‐based retrospective study was carried out at a tertiary care teaching hospital in South India. The hospital records of all pregnant women seeking MTP over a 2‐year period between January 2011 and December 2012 were reviewed. Results: A total of 244 women underwent MTP during the study period. More than one‐third (37.8%) were aged between 26 and 30 years. The majority of women underwent MTP during the first trimester (79.5%). Medical reasons were cited as the most common reason for undergoing MTP (39.3%), followed by unplanned pregnancy (34.8%). The majority of women were seeking MTP for the first time (84.8%). More than half of the women (52.9%) opted for post‐MTP contraception. Conclusion: MTP for unplanned pregnancy can be prevented if people are well informed about methods of contraception. MTP is an opportunity for healthcare professionals to discuss fertility needs and need for contraception with women seeking MTP so that appropriate decisions can be taken for suitable family planning.